Development, characterization and in vivo zinc absorption capacity of a novel soy meal hydrolysate-zinc complexes - Wang, Rongxin; Ye, Meijun; Zhu, Suyin; Zeng, Qingzhu; Yuan, Yang (Frontiers in Nutrition, 2023)
Background Zinc is an essential trace element for the human body. Recently, a novel Zn-binding peptide, Lys-Tyr-Lys-Arg-Gln-Arg-Trp (PP), was purified and identified from soy protein hydrolysates with high Zn-binding capacity (83.21 ± 2.65%) by our previous study. The preparation of soy meal hydrolysates (SMHs)-Zn complexes is convenient and low-cost, while PP (Lys-Tyr-Lys-Arg-Gln-Arg-Trp)-Zn complexes have a higher coordination rate but a relatively high cost. The aim of this study was to investigate the effect of soy meal hydrolysates (SMHs)-Zn complexes on zinc absorption in mice model, and synthetic soy peptide (PP)-Zn complexes with high Zn-binding capacity were used as control. Firstly, SMHs were prepared by enzymolysis, and the PP (Lys-Tyr-Lys-Arg-Gln-Arg-Trp) were synthesized based on previous studies. The binding mechanism of soy hydrolysates and zinc was analyzed by spectral analysis. Furthermore, the cytotoxicity of the SMHs-Zn complexes was also studied using the CCK-8 method. The effect of zinc absorption was evaluated based on Zn content, total protein and albumin content, relevant enzyme system, and the PeT1 and ZnT1 mRNA expression levels. Result The result showed that zinc was bound with carboxyl oxygen and amino nitrogen atoms on SMHs, with hydrophobic and electrostatic interactions as auxiliary stabilizing forces. SMHs-Zn were proved to have great solubility and a small particle size at different pH values, and it showed a beneficial effect on Caco-2 cells growth. Moreover, it was proved that SMHs-Zn and PP-Zn could increase the levels of zinc and the activity of Zn-related enzymes in mice. SMHs-Zn possessed higher PepT1 and ZnT1 mRNA expression levels than PP-Zn in the small intestine. Conclusion SMHs-Zn with a lower Zn-binding capacity had similar effects on zinc absorption in mice as PP-Zn, suggesting that the bioavailability of peptide-zinc complexes in mice was not completely dependent on their Zn-binding capacity, but may also be related to the amino acid composition.